AI-2 Induces Urease Expression Through Downregulation of Orphan Response Regulator HP1021 in Helicobacter pylori - Yang, Huang; Huang, Xiaoxing; Zhang, Xiaochuan; Zhang, Xiaoyan; Xu, Xiaohong; She, Feifei; Wen, Yancheng (Frontiers in Medicine, 2022)
Helicobacter pylori causes gastric infections in more than half of the world's population. The bacterium’s survival in the stomach is mediated by the abundant production of urease to enable acid acclimation. In this study, our transcriptomic analysis demonstrated that the expression of urease structural proteins, UreA and UreB, is induced by the autoinducer AI-2 in H. pylori. We also found that the orphan response regulator HP1021 is downregulated by AI-2, resulting in the induction of urease expression. HP1021 represses the expression of urease by directly binding to the promoter region of ureAB, ranging from -47 to +3 with respect to the transcriptional start site. The study findings suggest that quorum sensing via AI-2 enhances acid acclimation when bacterial density increases, and might enable bacterial dispersal to other sites when entering gastric acid.